Effects of inhaled ginger aromatherapy on chemotherapy-induced nausea and vomiting and health-related quality of life in women with breast cancer - Lua, Pei Lin; Noor Salihah, -; Nik Mazlan, Mamat (Churchill Livingstone, 2016)
Objective: To assess the efficacy of inhaled ginger aromatherapy on nausea, vomiting and health-related quality of life (HRQoL) in chemotherapy breast cancer patients.